Diseño e implementación de una aplicación psicopedagógica en Android para cadyuvar en la estimulación temprana en niños de 2 a 3 años en el MIES Fernando Ugarter de la Ciudad de Machala. - Pulla Tumbaco, Jonathan Manuel (2014)
In Children's Center of Good Living "Fernando Ugarte" (CIBV) City Machala, it has provided excellent service to the community with educational children's cognitive learning centers, Socio - Affective Language and allowing physical, academic and intellectual development children 2-3 years old.